Facebook users and undergraduates (Specially reference to Selected Universities in Sri Lanka) - Jayasekara, A.H.D. (International Journal of Scientific Research and Innovative Technology, 2015)
New media has play a pivotal role in enhance the relationship between the people and the media. Internet has pros and cons but more and more people all over the world using it for various purposes.Facebook is one of the largest online social network. In Sri Lankathere are more than 1.5 million Facebook users. Problems of this research were do Facebook users (undergraduates) use their account prudently and do they have enough knowledge on privacy settings.Objectives were to find out why the face book users reveal their privacy details through the account and found out whether the Facebook users are knowledgeable enough tosafe guard their privacy. This was Qualitative and Quantitative research. I used questionnaires and interviews to collect primary data. According to this research I came across most of the undergraduates were highly interested on Facebook. But they didn’t possess substantial knowledge about privacy settings.
Keywords: Internet; Privacy; Facebook; Cyber crime